2015
DOI: 10.1056/nejmoa1509255
|View full text |Cite
|
Sign up to set email alerts
|

Lixisenatide in Patients with Type 2 Diabetes and Acute Coronary Syndrome

Abstract: BACKGROUND: Cardiovascular morbidity and mortality are higher among patients with type 2 diabetes, particularly those with concomitant cardiovascular diseases, than in most other populations. We assessed the effects of lixisenatide, a glucagon-like peptide 1-receptor agonist, on cardiovascular outcomes in patients with type 2 diabetes who had had a recent acute coronary event. METHODS: We randomly assigned patients with type 2 diabetes who had had a myocardial infarction or who had been hospitalized for unstab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
361
0
10

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(376 citation statements)
references
References 36 publications
5
361
0
10
Order By: Relevance
“…Aside from BARI 2D, incident HF was either not directly adjudicated or the adjudication status was unclear. Additionally, these 5 other studies included non-specific definitions of new onset HF with 4 studies providing data for hospitalization for HF among patients without prior history of HF (28,29,31,32). The remaining study (EMPA-REG OUTCOME) reported data on introduction of loop diuretics during follow-up (24).…”
Section: Resultsmentioning
confidence: 99%
“…Aside from BARI 2D, incident HF was either not directly adjudicated or the adjudication status was unclear. Additionally, these 5 other studies included non-specific definitions of new onset HF with 4 studies providing data for hospitalization for HF among patients without prior history of HF (28,29,31,32). The remaining study (EMPA-REG OUTCOME) reported data on introduction of loop diuretics during follow-up (24).…”
Section: Resultsmentioning
confidence: 99%
“…The clinical trials of incretin-based therapies have not so far shown any preventive effect on CVD but were generally designed to show non-inferiority and may have preventive effects over longer time periods. [22][23][24] Studying various HbA 1c metrics offers clinicians compound perspectives on this biomarker with potentially differing purposes and utilities. The baseline HbA 1c provides the clinician with information on whether the glycaemic control at diagnosis already has a predictive value on complications at later stages.…”
Section: Discussionmentioning
confidence: 99%
“…After a median follow-up of 25 months, there was no difference in the primary composite endpoint of cardiovascular death, non-fatal MI, non-fatal stroke, or hospitalization for unstable angina between groups (13.4 vs 13.2%, HR 1.02, 95% CI 0.89-1.17, p=0.81 for superiority, p<0.001 for non-inferiority), and no difference in heart failure hospitalizations (4.0 vs 4.2%, HR 0.96, 95% CI 0.75-1.23) [47]. n the Liraglutide effect and action in diabetes: evaluation of cardiovascular outcome results (LEADER) trial, which randomized 9340 T2DM patients with high cardiovascular risk, liraglutide reduced the primary composite endpoint of cardiovascular death, non-fatal MI or non-fatal stroke compared to placebo after a median follow-up of 3.8 years (13 vs 14.9%, HR 0.8, 95% CI 0.78-0.97, p<0.001 for noninferiority; p=0.01 for superiority) [48].…”
Section: Glucagon-like Peptide-1 Agonistsmentioning
confidence: 99%